Current development in integrative therapy of traditional Chinese medicine for cancer treatment: A mini-review - Po-Hsuan Su; Chen-Jei Tai (Journal of Traditional and Complementary Medicine, 2020)
Cancer is a major public health problem worldwide, and there has been a sustained rise in its incidence in both developing and developed countries. Although there are currently numerous effective therapeutic options for cancer, they sometimes exhibit resistance and obvious side effects. Traditional Chinese medicine (TCM) currently plays a major role in cancer therapy by downregulating the growth of cancer cells through various pathways and by relieving side effects. Studies in cultured human malignant cell lines have demonstrated that Solanum nigrum can control cancer cell proliferation and cancer progression by inducing autophagic and apoptotic cell death. Case–control studies have indicated that TCM can relieve the side effects of cancer therapy. This review provides brief insights into the anticancer effects of TCM, the side effects relieved by TCM, and the role of TCM doctors in cancer treatment.